The Impact of Minimal Parental Involvement on Islamic Character Education in High School Students - Mulyati, Reni; Safira, Avril Nazwa; Dinillah, Dini Ilmi; Muktiali, Saiful; Juariah, Siti; Achmad, Listian Indriyani (DPPM Universitas Pelita Bangsa, 2023)
Parents are role models for their children and the family is also called the main foundation in the formation of disciplinary Islamic character in children. The purpose of this study is to analyze the impact of the lack of the role of parents in the education of children's disciplinary Islamic character. This research method uses a qualitative method with a field approach. The data collection technique is by means of direct observation, documentation and interviews using the resource persons of class X.X MAN 1 Bekasi students which amounted to 15 students, 1 BK teacher, and 3 parents. The results of the study show that all students say that it is the role of parents that is very important for their children, especially in the formation of disciplinary Islamic characters in students. The impact of the lack of the role of parents in Islamic character education on students is promiscuity around 46.6%, not respecting time by 33.3%, and participating in brawls around 20%.